H1N1 outbreak in a medical college of Pakistan: Implications of control in a resource poor setting - Mahmood, Syed Faisal; Kumar, Rohail; Jamal, Kishwar (International Journal of Infection Control, 2011)
Background: In early November 2009, a pandemic H1N1 virus infection outbreak occurred in a university setting of Karachi Pakistan. An unusually high number of students presented with ILI to the student health clinic and the emergency unit of Aga Khan University Hospital (AKUH) Karachi with a few requiring inpatient admission. We describe the clinical presentation and dynamics of this outbreak of suspected H1N1 as well as factors responsible for the outbreak and simple, cost-effective steps taken to tackle the situation. Methods: A brief self-administered questionnaire was distributed amongst students living in the university dorm and a case definition for presumed H1N1 was derived.Results: One hundred and forty nine of these students reported any of the asked symptoms in the month of November, out of which 58 met the case definition of presumed H1N1. The overall attack rate for ILI (influenza like illness) that describes our case definition of presumed H1N1 in November 2009 at AKUH hostels was 14%.Conclusion: In our study the initial lack of diagnostic facilities at the time of outbreak gives us limited information regarding the true number of H1N1 cases. In a resource limited setting, strategies such as communication and awareness can be most helpful in limiting the spread of the infection.